El imaginario de Vichy: feminidad y misión de las mujeres. Francia 1940-1944 - Moreno Rodríguez, Beatriz (Cuadernos de Historia Contemporánea, 2006)
The current article deals with the place of women in the social and political project implanted by the Vichy Goverment during the Nazi occupation (1940-1944). It also approaches the development of the particular model of feminity valid in that period, as well as its social function.. These subjects are approached through the study of the historical sources (literary, journalistic and legal documents), together with the suitable scientific bibliography. The current work shows up the process of re-allocation of women to the domestic sphere and reproductive function (in a material level), as well as their re assignation as a guarantee for morals and social order (in a simbolic level), considering that both sorts of re-allocation took place through specific legal measures, besides the recovery of political, cultural, social and religious elements in a traditional sort of way.